Persepsi Mahasiswa Semester Akhir Ilmu Komunikasi Universitas Bengkulu Mengenai Dunia Kerja Melalui Tiktok @vmuliana - Hutasoit, Elvana Melania; Budiman, Dwi Aji; Makhrian, Andy (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This research aims to discuss meaning through in-depth interviews with final semester communication science students at Bengkulu University regarding the world of work through TikTok @vmuliana, the presence of the TikTok @vmuliana account aims to provide solutions to all problems of readiness to enter the world of work. Research using Stuart Hall's reception method from the encoding and decoding model with a dominant position and a negotiation position shows that the intensity of exposure to @vmuliana TikTok content has a significant relationship with students' perceptions of preparing to enter the world of work. The existence of differences in the meaning of informants is influenced by contextual factors for each informant, such as background, social norms and values, and the condition and experience of the informant. This research provides knowledge regarding the role of social media as an information learning tool, especially in preparing students to face the world of work. Researchers collected data through interviews with research subjects, Bengkulu University communication science student class 20 and followers of the @vmuliana account and conducted interviews lasting 5-10 minutes. And through research results, it can be found that students who have good digital literacy are better able to filter and utilize information from social media for their career needs and content that discusses skills, challenges and career tips such as the @vmuliana account really helps students understand reality and improve their readiness to enter the world of work